Dihalogeno(diphosphane)metal(II) complexes (metal = Co, Ni, Pd) as pre-catalysts for the vinyl/addition polymerization of norbornene - elucidation of the activation process with B(C6F5)(3)/AlEt3 or Ag[closo-1-CB11H12] and evidence for the in situ formation of "naked" Pd2+ as a highly active species - Lassahn, P; Lozan, V; Wu, B; Weller, A; Janiak, C (2003)
Dihalogenometal(II) complexes with bidentate phosphane ligands of the general type [M{Ph2P(CH2)nPPh2} X2] with n = 2 to 5, X = Cl or Br and M = Co, Ni or Pd have been utilized as catalysts for the vinyl/addition polymerization of norbornene. These complexes can be activated with the Lewis-acids methylalumoxane (MAO) or tris(pentafluorophenyl)borane, B(C6F5)3 in combination with triethylaluminium (AlEt3). The nickel(II) and palladium(II) complexes show very high polymerization activities up to 107 gpolymer molmetal-1 h-1. Yet, the complexes Pd(dppe)Cl2 (5, 1.9 × 107 gpolymer molPd-1 h-1) and Pd(dppp)Cl2 (6, 3.0 × 103 gpolymer molPd-1 h-1) demonstrated that small changes in the ligand structure could have great effects on the polymerization activity [dppe = 1,2-bis(diphenylphosphino)ethane, Ph2P(CH2)2PPh2; dppp = 1,3-bis(diphenylphosphino)propane, Ph2P(CH2)3PPh2]. The activation process of the pre-catalysts 5 and 6 in combination with B(C6 F5)3/AlEt3 was followed by multinuclear (1H, 19F, and 31P) NMR investigations and by reaction with B(C6 F5)3 and Ag[closo-1-CB11H12]. The reaction of B(C6F5)3 and AlEt3 leads to an aryl/alkyl group exchange resulting in the formation of AlEt3-n(C6F5)n and B(C6F5)3-nEtn with Al(C6F5)3 and BEt3 as main products for an about equimolar ratio. AlEt3-n(C6F5)n will then react with the pre-catalysts and abstract the chloride atoms to form [M{Ph2 P(CH2)nPPh2}]2+ as the active species for the polymerization. The higher polymerization activity of 5/B(C6F5)3/AlEt3 compared to 6/B(C6F5)3/AlEt3 can be explained by a ligand redistribution reaction of unstable [PdII (dppe)]2+ to give inactive and isolable [PdII(dppe)2]2+ and highly active, "naked" Pd2+ cations together with the lower coordinating ability of the anionic adduct [Cl-Al(C6F5)3]- in comparison to [Cl-B(C6F5)3]-. The Lewis-acid Al(C6F5)3 is much more activating than B(C6F5)3. The [Pd(dppe)2]2+ cation from the ligand redistribution was isolated in the (X-ray) structurally elucidated compounds [PdII(dppe)2]-[ClB(C6 F5)3]2·4CH2Cl2 and [PdII(dppe)2][CB11 H11Cl]2·3CH2Cl2. The stable [Pd(dppp)]2+ cation from 6 could be crystallized as [PdII(dppp)(CB11H12)] [CB11H12] (CB11H12 = mono-anionic carborane [closo-1-CB11H12]-).